2016
DOI: 10.1590/1089-6891v17i330941
|View full text |Cite
|
Sign up to set email alerts
|

Características De Carcaça E Qualidade Da Carne De Cordeiros Alimentados Com Diferentes Teores De Torta De Soja Em Substituição Ao Farelo De Soja

Abstract: ResumoObjetivou-se avaliar a substituição do farelo de soja pela torta de soja sobre as características de carcaça e qualidade da carne de cordeiros Santa Inês. Foram utilizados 29 machos inteiros, com 23,63 ± 2,44 kg de peso vivo, 80 dias de idade, distribuídos de maneira inteiramente casualizada, submetidos a cinco dietas, sendo que as dietas variaram nos teores de substituição do farelo de soja pela torta de soja de 0, 25, 50, 75 e 100%. Para cada teor de substituição foram utilizados seis animais, mas no t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
6
9
0
5
Order By: Relevance
“…This result corroborates with the lower indexes presented by pasture-finished animals. Grandis et al (2016) found similar commercial cut proportions compared to those of this study. Mcmanus et al (2013) observed that Santa-Inês lambs had an average half carcass weight of 7.09 kg, similar to that of lambs finished on pasture, and inferior to that of the other systems in this study.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This result corroborates with the lower indexes presented by pasture-finished animals. Grandis et al (2016) found similar commercial cut proportions compared to those of this study. Mcmanus et al (2013) observed that Santa-Inês lambs had an average half carcass weight of 7.09 kg, similar to that of lambs finished on pasture, and inferior to that of the other systems in this study.…”
Section: Resultssupporting
confidence: 85%
“…Queiroz et al (2015) found higher UFT and SFT values (2.97 mm and 3.02 mm, respectively) in Santa Inês lambs finished in feedlot and slaughtered upon reaching the average live weight of 33 kg, with average age of 155 days. Grandis et al (2016), assessing male, uncastrated Santa Inês lambs fed different amounts of soybean cake, observed average mean value for LEA of 14.60 cm 2 , and 2.53 mm for SFT. The different results for SFT may derive from the difference between diet composition, slaughter weights and genetic groups.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…No significant differences were observed (P>0.05) for the water loss under pressure among glycerin crude levels, with an average of 25.99 g 100 g -1 (Table 4). According to Grandis et al (2016), in a study evaluating the use of soybean cake as a substitute for soybean meal, differences in water loss under pressure were not also verified, with mean values of 19.4 g 100g -1 .…”
Section: Parametersmentioning
confidence: 97%
“…Cordeiros provenientes de animais de genótipos com peso adulto elevado apresentam-se menos maduros em determinado peso, quando comparados com animais de genótipos com menor peso adulto. Dessa maneira, o peso ideal de abate deve levar em consideração as características desejáveis da carcaça como: porcentagem de ossos, gordura e músculos, cobertura de gordura, entre outros, para cada raça, visando atender às exigências do mercado consumidor (Bezerra et al, 2010 Grandis et al (2016) citam que a faixa de peso para que encontrem adequadas deposições de gordura em ovinos Santa Inês encontra-se entre 15 e 35kg de peso vivo, pois acima deste peso ocorre deposição acentuada de gordura. Já Santos et al, (2001) constataram melhores resultados para a relações músculo:osso e relação músculo:gordura, numa faixa de peso vivo 25 e 35kg, observando a partir deste peso comportamento decrescente na quantidade de músculo em relação à quantidade de gordura, à medida que os cordeiros se desenvolvem.…”
Section: Peso E Idade De Abateunclassified